The inhibition of malignant epithelial cells in mucosal injury in the oral cavity of strains by pomegranate fruit extract (Punica granatum linn) through Bcl-2 expression - Sri Hernawati (Dental Journal (Majalah Kedokteran Gigi), 2013)
Background: Squamous cell carcinoma of oral cavity is a malignant neoplasms derived from epithelia. The malignant neoplasms are cells that have changed their structure and function, and their number becomes increasing abnormally, invasive, and metastatic. Carcinoma can be caused by the resistance of malignant cell apoptosis. Bcl-2 is a proto-oncogene of Bcl family that inhibits the process of cell apoptosis and suppresses Bax protein (pro-apoptotic). The management efforts of cancer diseases, however, still have many obstacles. Thus, the researcher was triggered to explore more herbal plants, namely pomegranate. Pomegranate as a medicinal plant is accessible and cheap. Ellagic acid (EA) is a single active compound derived from whole pomegranate fruit extract (PGL), which has anti-cancer activity as in vitro, but EA is low concentration in plasma, low water solubility, and insoluble in intestinal. These facts prompted the researcher to compare between pomegranate extract, which consists of several active compounds, and that, which only consists of ellagic acid. Thus, this research is expected to know how some active compounds can work synergistically in the PGL, so the effect can be more potent. Purpose: The purpose of this research, therefore, was to compare EA with PGL in reducing the expression of Bcl-2. Methods: This laboratory experimental research was used 32 male mice (Balb/c) in the age of 5 months. They were randomly divided into 4 groups: 2 control groups (K0: which was not exposed with benzopirene and also untreated and K1: which was exposed with benzopirene and also untreated), 2 treatment groups (P1: which was exposed with benzopirene and also treated with EA and P2: which was exposed with benzopirene and also treated with the PGL). Next, an examination was conducted by using immunohistochemical techniques. results: The results then showed that the provision of the PGL could decrease the expression of Bcl-2 significantly higher than that of EA in the malignant epithelial cells of the oral mucosa of those mice. Conclusion: It may be concluded that the provision of the PGL can kill malignant cells in the oral cavity of mice by increasing apoptosis through decreasing Bcl-2 expression that was higher than the provision of EA.latar belakang: Karsinoma sel skuamosa rongga mulut adalah istilah yang digunakan menyebut neoplasma ganas berasal dari epitel. Neoplasma ganas adalah sel yang telah berubah struktur dan fungsi, sehingga mengalami peningkatan jumlah secara abnormal,invasif dan metastasis. Terjadinya karsinoma salah satu disebabkan oleh karena hambatan apoptosis terhadap sel ganas. Bcl-2 adalah protoonkogen keluarga Bcl yang berperan menghambat proses apoptosis sel dan bekerja menekan protein Bax (pro apoptosis). Berbagai upaya penatalaksanaan penyakit kanker masih banyak menemui kendala,sehingga peneliti menggali tanaman obat yaitu buah delima. Buah delima sebagai tanaman obat, mudah didapat dan harganya murah. Ellagic acid (EA) senyawa tunggal bahan aktif dari ekstrak buah delima yang memiliki aktivitas sebagai anti kanker secara in-vitro tetapi EA aktivitas dan konsentrasinya dalam plasma rendah, kelarutan dalam air rendah, metabolisme (EA) tidak larut dalam intestinal. Fakta ini mendorong peneliti untuk membandingkan dengan whole ekstrak delima (PGL) yang terdiri dari beberapa senyawa bahan aktif, tidak hanya ellagic acid, memungkinkan beberapa senyawa bahan aktif pada PGL bisa bekerja sinergis, sehingga efeknya lebih poten. tujuan: Tujuan penelitian ini membandingkan antara EA, dengan whole ekstrak buah delima (PGL) dalam menurunkan ekspresi Bcl-2. Metode: Metode penelitian yang digunakan adalah eksperimental laboratories, 32 ekor mencit (Balb/c), jantan, umur 5 bulan dibagi secara random menjadi 4 kelompok, 2 kelompok kontrol (K0: tidak dipapar benzopirene dan tidak diberi perlakuan, K1: dipapar benzopirene dan tidak diberi perlakuan), 2 kelompok perlakuan (P1: dipapar benzopirene dan diberi EA, P2: dipapar benzopirene dan diberi PGL). Pemeriksaan dengan menggunakan teknik imunohistokimia. hasil: Hasil penelitian menunjukkan bahwa pemberian PGL dapat menurunkan ekspresi Bcl-2 lebih tinggi dibandingkan EA pada sel epitel ganas mukosa rongga mulut mencit. Kesimpulan: Kesimpulan penelitian ini adalah pemberian PGL dapat membunuh sel ganas pada rongga mulut mencit dengan jalan meningkatkan apoptosis melalui penurunan ekspresi Bcl-2 lebih tinggi dibandingkan pemberian EA.